Biomethanation of vegetable market waste in an anaerobic baffled reactor: Effect of effluent recirculation and carbon mass balance analysis. (September 2016) - Gulhane, Madhuri; Khardenavis, Anshuman A.; Karia, Sneha; Pandit, Prabhakar; Kanade, Gajanan S.; Lokhande, Satish; Vaidya, Atul N.; Purohit, Hemant J.
Graphical abstract: Highlights: Sustainable biogas production from vegetable market waste in an ABR. Phase separation in the chambers remained undisturbed in spite of effluent recirculation. Enhanced biogas production due to complete utilization of residual VFAs during recirculation. Carbon recovery factor for mass balance able to account for nearly 96.7% of input carbon. One of the highest methane yield of 0.42–0.0.52 L methane/g VS added/d from vegetable waste in ABR. Abstract: In the present study, feasibility of biomethanation of vegetable market waste in a 4-chambered anaerobic baffled reactor (ABR) was investigated at 30 d hydraulic retention time and organic loading rate of 0.5 g VS/L/d for one year. Indicators of process stability viz., butyrate/acetate and propionate/acetate ratios were consistent with phase separation in the different chambers, which remained unaltered even during recirculation of effluent. Chemical oxygen demand (COD) and volatile solids (VS) removal efficiencies were observed to be consistently high (above 90%). Corresponding biogas and methane yields of 0.7–0.8 L/g VS added/d and 0.42–52 L/g VS added/d respectively were among the highest reported in case of AD of vegetable waste in an ABR. Process efficiency of the ABR for vegetable waste methanation, which is indicated by carbon recovery factor showed that, nearly 96.7% of the input carbon considered for mass balance was accounted for in the product.